Morphological and molecular identification of citrus mealybug (Planococcus citri) and its response to selected fermented plant extracts - Gul, Khadem Ahad (2021)
This project was conducted to evaluate the effect of FPEs against P. citri. Prior to carry out research on the FPEs, the mealybugs collected from citrus plants were confirmed as P. citri based on their morphological characteristics and genes analysis such as Internal transcribed spacer (ITS2), 18S ribosomal and Cytochrome c oxidase I (COI) mitochondrial genes. A total of 10 plant materials were selected for FPEs study based on their toxicity and repellent efficacy, namely onion, garlic, turmeric, aromatic ginger, lemongrass, variegated mint, Mexican mint, peppermint, kaffir lime and lime. Among the tested FPEs, the fermented Mexican mint extract, fermented turmeric extract and fermented onion extract were highly disruptive on P. citri with more than 80% mealybugs died after 120 hours post treatment. The fermented Mexican mint extract tested in this study was the best FPE in causing mortality to P. citri, however it was the least effective repellent to P. citri among the FPEs. Fermented Mexican mint extract, fermented turmeric extract and fermented onion extract had scored less than 10% (w/v) LC50 value while other FPEs had required more than 10% (w/v) to induce 50% morality of P. citri after 72 hours post treatment. The fermented variegated mint was the best repellent to P. citri. When the FPE concentration was increased to 10% (w/v), fermented garlic extract, fermented kafir lime extract and fermented onion extract had caused higher repellency percentage to P. citri than fermented lime extract, fermented turmeric extract, fermented Mexican mint extract, fermented peppermint extract, fermented aromatic ginger extract and fermented lemongrass extract. The phytotoxic effect of these FPEs was recorded after 24, 48 and 72 hours post treatment. Concentration of FPEs at 5% (w/v) and 10% (w/v) did not induce phytotoxicity to citrus leaves after 24, 48 and 72 hours post treatment. Fermented Mexican mint extract had induced higher phytotoxic effect to citrus leaves compared to the fermented turmeric extract and fermented onion extract at different time intervals. The severity level of the phytotoxic effect caused by fermented Mexican mint extract increased with time and concentrations, and became severe after 72 hours post treatment. The mealybug wax was detached after treated with FPE concentrations above 10% (w/v). With increasing concentration and time of FPE treatment, the yield of wax was also increased. The fermented onion extract showed the highest mealybug wax gained compared to other FPEs and also the chloroform after 30 seconds and 60 seconds post treatment. The fermented turmeric extract performed better than chloroform after 30 seconds post treatment, but the performance dropped after 60 seconds post treatment. The fermented Mexican mint extract had the least effect on the mealybug wax among the tested FPEs in this study. As a conclusion, the present research findings have revealed the potential use of FPEs in controlling P. citri. The fermented Mexican mint, turmeric and onion extracts are a good candidate for controlling P citri while the fermented variegated mint extract is a good repellent among the tested FPEs. These findings are new and novel for biopesticide development. With further investigation on the chemical composition and mode of action of the FPE will enable the selection of functional FPE in citrus mealybug control.